BENTUK PENYIMPANGAN KAIDAH IMLAIYYAH DAN KHATHTHIYAH HIASAN SENI KALIGRAFI MASJID DI PADANG PARIAMAN - Siti Aisyah (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
The purpose of this study was to determine the forms of irregularities in the principles of imlaiyah and khathtiyah and to explain the impact of these forms of deviation. Qualitative research methods with a socio-cultural approach to documentation and interview techniques. After doing the research, it turns out that the form of irregularities in the rules of Islamic and khaththiyah is quite a lot found in several Padang Pariaman mosques. The form of mosque calligraphy decoration which deviates from the imlaiyyah rules in Padang Pariaman such as the writing of words / sentences that are lacking and excessive in letters, writing that is lacking dots and over writing the sign of the gift. While the form of mosque calligraphy decoration that deviates from the rules of khaththiyah in Padang Pariaman mosque such as writing the shape and size of letters that are not exactly in shape with the type of calligraphy form, including the mixing of types of rules made in one sentence of writing. If the form of irregularities is allowed to have an impact on the self-esteem of the community itself in the view of the general public. The existence of the mosque decoration is considered to have neglected the writing of the Qur'anic verse because the result of the error in the mosque decoration has damaged the meaning of the sentence of the Qur'an and the form of its writing, also decreasing the value of the beauty of the mosque, as well as reflecting the lack of knowledge and ability of the community in the field of al- Qur'an and calligraphy, and bequeath the wrong writing culture to generations afterwards.